1991
DOI: 10.1038/bjc.1991.263
|View full text |Cite
|
Sign up to set email alerts
|

The influence of serum methotrexate concentrations and drug dosage on outcome in childhood acute lymphoblastic leukaemia

Abstract: Summary Sequential methotrexate (Mtx) absorption studies were undertaken in 127 children undergoing treatment for childhood non-T acute lymphoblastic leukaemia (ALL) to determine whether serum drug concentration, clearance and dosage affect event free survival (EFS). Higher serum concentration and area under the plasma concentration curve (AUC) were not associated with an improved EFS. Methotrexate clearance was not found to be of prognostic significance.Patients who tolerated only low 6-mercaptopurine (6-MP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This finding was true for both girls and boys and was not influenced by the administration of intensification blocks. This confirms the findings of smaller earlier studies where children who became neutropenic during treatment had a lower risk of late relapse (Pearson et al, 1991;Dolan et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
“…This finding was true for both girls and boys and was not influenced by the administration of intensification blocks. This confirms the findings of smaller earlier studies where children who became neutropenic during treatment had a lower risk of late relapse (Pearson et al, 1991;Dolan et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
“…Considering that the prognosis of ALL is worst in infants [3,4] and that MTX clearance, although the observations are limited to a small number of patients, seems equivalent to or slightly higher than in older children, it can be suggested that full MTX doses can and should be given even to the very young child without a high risk of toxicity, with the aim of maximizing the antileukemic effect [26].…”
Section: Discussionmentioning
confidence: 99%
“…1, 2). Importantly, patients tolerant to the starting doses of 6MP and MTX, but for whom maintenance therapy is not intensified, have a poorer outcome compared both with patients who receive reduced drug doses due to leukopenia and with those who are upward dose adjusted to obtain target myelosuppression 36–38,62,63. Furthermore, recurrent unwarranted treatment interruptions due to a rise in aminotransferases are also an adverse factor for risk of relapse 37.…”
Section: Drug Dosagementioning
confidence: 99%